Pelatihan Membangun Website Kampung Sejarah Lubang Jepang Sebagai Pengetahuan Sejarah dan Menambah Destinasi Wisata Di Kota Padang - Anip Febtriko; Harlan Kurnia AR; Refli Noviardi; Tri Rahayuningsih (Universitas Lancang Kuning, 2022)
Based on the Padang City Government meeting with the Padang Higher Education LPPM on November 11, 2021 with the theme of accelerating regional development through the development of thematic villages in the city of Padang, it is planned to provide training and assistance to the community of the slopes of the Tabing Banda Gadang Village. Where at this time there is no website as a tool for knowledge of historical information and historical documentation as well as a promotional tool to increase tourist destinations in the city of Padang. The method in this service is to make observations which include interviews with partners, make preparations by making website applications, carry out implementation by providing training on building websites, and evaluating the results of this service by giving questionnaires to determine the level of satisfaction from the website. . The purpose of this service activity is to help the Padang city government and its people in documenting the history of this Japanese hole as well as a promotional medium to improve tourist destinations through the provision of this website training.